2010
DOI: 10.1371/journal.pone.0015701
|View full text |Cite
|
Sign up to set email alerts
|

A Mitosis Block Links Active Cell Cycle with Human Epidermal Differentiation and Results in Endoreplication

Abstract: How human self-renewal tissues co-ordinate proliferation with differentiation is unclear. Human epidermis undergoes continuous cell growth and differentiation and is permanently exposed to mutagenic hazard. Keratinocytes are thought to arrest cell growth and cell cycle prior to terminal differentiation. However, a growing body of evidence does not satisfy this model. For instance, it does not explain how skin maintains tissue structure in hyperproliferative benign lesions. We have developed and applied novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
124
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 71 publications
13
124
0
Order By: Relevance
“…11 Mitosis kinases Aurora B or Polo-like kinase 1 (Plk1), which are involved in chromosome segregation, participate in the mitotic spindle checkpoint 32,33 and some of their inhibitors are being tested in cancer clinical trials. 34 To explore whether the keratinocyte mitotic checkpoints are involved in the signal to differentiation, we inhibited these molecules by specific chemical inhibitors.…”
Section: Mitosis Block and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Mitosis kinases Aurora B or Polo-like kinase 1 (Plk1), which are involved in chromosome segregation, participate in the mitotic spindle checkpoint 32,33 and some of their inhibitors are being tested in cancer clinical trials. 34 To explore whether the keratinocyte mitotic checkpoints are involved in the signal to differentiation, we inhibited these molecules by specific chemical inhibitors.…”
Section: Mitosis Block and Differentiationmentioning
confidence: 99%
“…We have previously shown that postmitotic keratinocytes continue DNA synthesis and become polyploid during differentiation in vitro 9 and in vivo, 10,11 and that the process of endoreplication is stimulated by MYC. As for MYC, other molecules involved in cell cycle progression caused epidermal hyperplasia, but were not able to disrupt differentiation (for example, E2F, Cyclin D1, MDM2, cdk2, cdk4; references in Zanet et al 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might help explain why, following exit from mitotic SAC arrest, some cell types undergo cell death, while others can continue to cycle or potentially differentiate into nondividing polyploid cells. [2][3][4]9 In the case of A. nidulans, which normally maintains multiple nuclei within a syncytium, the failed mitosis which occurs during SIME is tolerated. This is because the genome of syncytial cells normally doubles each cell cycle and this still occurs when mitosis fails and cells undergo SIME.…”
mentioning
confidence: 99%
“…Somatic polyploidy has several advantages for the affected cells including a better response to metabolic and/or genotoxic stress and a lower sensibility to apoptotic stimuli. 10,11,20,21 In mammals and higher vertebrates different cell types have been shown to be polyploid, including trophoblast giant cells, 10,11,,22 hepatocytes, 23,24 megakaryocytes, 25 keratinocytes, 26 and vascular smooth cells. 27 Endoreplication represents a major mechanism leading to developmental programmed somatic polyploidy.…”
Section: Introductionmentioning
confidence: 99%